Entry Efficiency, Protease Dependence, and Antibody-Mediated Neutralization of SARS-CoV-2 Sublineages KP.3.1.1 and XEC - Arora, Prerna; Kempf, Amy; Nehlmeier, Inga; Schulz, Sebastian; Jäck, Hans-Martin; Hoffmann, Markus; Pöhlmann, Stefan (Vaccines, 2025)
Background: The SARS-CoV-2 variants KP.3.1.1 and XEC currently dominate the COVID-19 epidemic. However, their cell tropism, proteolytic processing, and susceptibility to neutralization by monoclonal antibodies remain incompletely characterized. Methods: We employed pseudotyped viruses to assess the entry efficiency of KP.3.1.1 and XEC in various cell lines, their dependence on TMPRSS2 for lung cell entry, and their ability to use ACE2 for infection. Additionally, we evaluated their susceptibility to neutralization by monoclonal antibodies BD55-4637 and BD55-5514. Results: KP.3.1.1 and XEC entered cell lines with similar efficiency as the parental JN.1 lineage and utilized TMPRSS2 for Calu-3 lung cell entry. Unlike JN.1, KP.3.1.1 and XEC failed to efficiently use murine ACE2 for cell entry. Both variants were effectively neutralized by the monoclonal antibodies BD55-4637 and BD55-5514, suggesting therapeutic potential. Conclusions: Our findings demonstrate that JN.1, KP.3.1.1, and XEC, like their predecessor BA.2.86, rely on TMPRSS2 for lung cell entry and remain sensitive to certain neutralizing monoclonal antibodies. However, these variants differ in their ability to utilize ACE2 species orthologs for cell entry.
CRIS-Team Scopus Importer:2025-05-09
Keywords: BA.2.86 descendants; cell tropism; monoclonal antibody susceptibility; SARS-CoV-2 variants